2004
DOI: 10.1121/1.1736271
|View full text |Cite
|
Sign up to set email alerts
|

The effect of loading on disturbance sounds of the Atlantic croaker Micropogonius undulatus: Air versus water

Abstract: Physiological work on fish sound production may require exposure of the swimbladder to air, which will change its loading (radiation mass and resistance) and could affect parameters of emitted sounds. This issue was examined in Atlantic croaker Micropogonius chromis by recording sounds from the same individuals in air and water. Although sonograms appear relatively similar in both cases, pulse duration is longer because of decreased damping, and sharpness of tuning (Q factor) is higher in water. However, pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 16 publications
4
37
0
Order By: Relevance
“…Sharpness of tuning increases in water. Many of these differences parallel findings from Atlantic croaker recorded in both media (Fine et al, 2004). Peak frequency in croaker sounds does not differ between air and water because it is determined by sonic muscle contraction-relaxation time, which is not affected by acoustic loading.…”
Section: Discussionsupporting
confidence: 63%
“…Sharpness of tuning increases in water. Many of these differences parallel findings from Atlantic croaker recorded in both media (Fine et al, 2004). Peak frequency in croaker sounds does not differ between air and water because it is determined by sonic muscle contraction-relaxation time, which is not affected by acoustic loading.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast to stridulation sounds, duration of drumming sounds did not decrease with time. Fine et al (Fine et al, 2004) found a longer pulse duration in drumming sounds emitted in water in the sciaenid Micropogon undulates, but no change in sound duration.…”
Section: Sound Durationmentioning
confidence: 98%
“…This change in sound duration and subsequently pulse periods is probably due to muscle fatigue. This indicates that in distress sounds temporal patterns are less important for communication than they are in reproductive behaviour (Myrberg et al, 1978;Fine et al, 2004).…”
Section: Sound Durationmentioning
confidence: 99%
See 2 more Smart Citations